2018
DOI: 10.1016/j.clinbiomech.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acromiohumeral distance in symptomatic and asymptomatic patient shoulders and those of healthy controls

Abstract: Differences in shoulder pain perception at 0° are not attributable to acromiohumeral distance differences. However, treatments focused on increasing AHD at 60° could be prescribed, as a significantly reduced AHD was found in symptomatic shoulders when compared with contralateral shoulders. Further research is needed to determine, not only static differences in AHD, but also dynamic differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
(56 reference statements)
0
26
0
1
Order By: Relevance
“…Another common reason for exclusion was that the participants were not diagnosed with SAPS. Fifteen studies met the inclusion criteria; nine of the 15 addressed the first aim 21,29,31,32,[52][53][54][55][56] , three addressed the second aim 54,57,58 and six addressed the final aim 29,32,[59][60][61][62] . Of the nine studies that addressed the first aim, one also addressed the second aim 54 and two addressed the third aim 29,32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another common reason for exclusion was that the participants were not diagnosed with SAPS. Fifteen studies met the inclusion criteria; nine of the 15 addressed the first aim 21,29,31,32,[52][53][54][55][56] , three addressed the second aim 54,57,58 and six addressed the final aim 29,32,[59][60][61][62] . Of the nine studies that addressed the first aim, one also addressed the second aim 54 and two addressed the third aim 29,32 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 775 participants were included across the 15 studies (Tables 1, 2, and 3). In the nine studies that addressed the first aim 21,29,31,32,[52][53][54][55][56] , 472 participants were included (mean age (SD) ranging between 23 (4) and 65 (10) years). Three of nine studies (170 participants) only included athletes, drawn from a variety of sports [54][55][56] , and the remaining studies included the general population.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The causes of impingement syndrome are possibly multifactorial 23 . In a study AHD measurement was found decreased at 60° abduction position in patients with shoulder pain 24 . In another study AHD measurement was found to have a small association with shoulder pain, function and range of motion at 0 and 60° in patients with rotator cuff‐related shoulder pain 25 …”
Section: Discussionmentioning
confidence: 99%